A series of esters of diastereomeric menthols: Comprehensive mass spectral libraries and gas chromatographic data. (1st November 2021) - Dekić, Milan S.; Radulović, Niko S.; Selimović, Enisa S.; Boylan, Fabio
Graphical abstract: Highlights: A series of esters of diastereomeric menthols was analyzed by GC–MS. A foolproof identification procedure for these aroma important esters was suggested. EI Mass Spectral Libraries recorded on SQ and QIT mass detectors were created. GC RI data on non-polar HP-5MS and polar HP-Innowax columns are included therein. A collection of MS and GC data was compiled and is available as supplementary data . Abstract: A comprehensive data collection of mass spectral and gas chromatographic data of a series of esters of diastereomeric menthols (menthol, isomenthol, neomenthol, and neoisomenthol), in total 150 chemical entities, obtained by GC–MS on commonly used capillary columns of different polarity (non-polar HP-5MS and polar HP-Innowax), was created. Also, MS libraries containing electron ionization MS recorded on single quadrupole as well as on quadrupole ion-trap mass detectors together with the RIs on non-polar and polar columns were compiled (available as supplementary material s). The results point out to frequent misidentification of neoisomenthyl acetate as isomenthyl acetate in the literature, and the means of how to resolve this issue was suggested. The outcomes of this study provide chemists and food technologists with a useful tool in the field of food analysis of compounds with important food aroma properties.